2008
DOI: 10.1093/hmg/ddn057
|View full text |Cite
|
Sign up to set email alerts
|

Myopathy with lactic acidosis is linked to chromosome 12q23.3-24.11 and caused by an intron mutation in the ISCU gene resulting in a splicing defect

Abstract: We describe the mapping and identification of the gene for hereditary myopathy with lactic acidosis (HML). HML is characterized by low physical performance, resulting in physical exertion that causes early exhaustion, dyspnoea and palpitations. Using an autosomal recessive mode of inheritance, we mapped the trait to chromosome 12q23.3-24.11, with a maximum lod score of 5.26. The 1.6-Mb disease-critical region contained one obvious candidate gene-ISCU-specifying a protein involved in iron-sulphur cluster assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
72
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 14 publications
1
72
0
1
Order By: Relevance
“…This disorder is characterized by muscle weakness, exercise-induced myoglobinuria, and muscle iron overload. 41,42 ISCU is a key protein involved in Fe-S cluster biogenesis, and isoforms originating from alternative splicing have been found in the mitochondria and the cytosol, indicating that Fe-S cluster biogenesis is a compartmentalized process in mammalian cells. 48,50 Impairment of cytosolic Fe-S cluster assembly after selective depletion of cytosolic ISCU in HeLa cells indicated that its function cannot be compensated by mitochondrial ISCU.…”
Section: Discussionmentioning
confidence: 99%
“…This disorder is characterized by muscle weakness, exercise-induced myoglobinuria, and muscle iron overload. 41,42 ISCU is a key protein involved in Fe-S cluster biogenesis, and isoforms originating from alternative splicing have been found in the mitochondria and the cytosol, indicating that Fe-S cluster biogenesis is a compartmentalized process in mammalian cells. 48,50 Impairment of cytosolic Fe-S cluster assembly after selective depletion of cytosolic ISCU in HeLa cells indicated that its function cannot be compensated by mitochondrial ISCU.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, impaired functions of XPD/ Ercc2 and FancJ/Bach1 lead to a certain type of xeroderma pigmentosum (35) and to Fanconi's anemia (67), respectively. Since more and more diseases are identified to be related to an impaired assembly of Fe/S proteins, including Friedreich's ataxia (52) and X-linked sideroblastic anemia and cerebellar ataxia (2), as well as some forms of myopathies (44,49), microcytic anemia (11), and erythropoietic protoporphyria (59), the elucidation of the mechanisms leading to the maturation of Fe/S proteins within various eukaryotic compartments is of utmost medical importance. The identification of huNbp35 as a critical component of the cytosolic CIA machinery for Fe/S protein maturation may help to achieve deeper insights into these mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Although these [Fe-S] synthetic components work at different points in the same pathway, different phenotypes arise from inherited mutations in these genes, including Friedreich ataxia (FRDA) (20,21), ISCU myopathy (22,23), and the recently characterized sideroblastic anemia (SA), associated with a mutation in glutaredoxin 5 (GLRX5) (24). The patient with GLRX5 deficiency and SA has an A294G mutation in the last nucleotide of exon-1, which impedes intron-1 splicing and dramatically reduces GLRX5 mRNA levels.…”
Section: Introductionmentioning
confidence: 99%